(untitled) (Asian Journal of Agriculture, 2025)
Abstract. Ridwansyah R, Prihatiningsih N, Lestari P, Kharisun, Djatmiko HA, Irwandhi. 2025. Diversity analysis of soil microbial communities in Inpari 32 rice fields following indigenous endophytic bacteria applications. Asian J Agric 9: 245-254. The challenge of rice farming in Indonesia is exacerbated by land degradation resulting from the use of chemical fertilizers and pesticides, which is further intensified by climate change. The use of endophytic bacteria in rice farming is an environmentally friendly and sustainable approach that increases microbial diversity and soil productivity. This study investigates the effects of indigenous endophytic bacterial applications on soil microbial diversity in Inpari 32 rice (Oryza sativa L.) fields. The study involved the application of indigenous endophytic bacteria to rice plants, the isolation and characterization of soil bacteria following application, and the evaluation of microbial diversity using the Shannon-Wiener diversity index. A hypersensitivity test was conducted to assess the safety and compatibility of the plant with bacteria. The study applied the endophytic bacterial formula evenly to the lower and upper surfaces of rice leaves using a sprayer, with treatments administered five times at 56, 62, 67, 72, and 77 days after planting. The results demonstrated that the treatment enhanced the diversity of soil microbial, including genera such as Paenibacillus, Micrococcus, Methylobacterium, Streptomyces, Actinomyces, Acremonium, and Penicillium. The diversity index indicated that treatments from: (i) Petanahan Kebumen; (ii) Karangwangkal Banyumas; (iii) Sumbang Banyumas, and the consortium; (iv) fell into the moderate diversity category. The hypersensitivity test revealed that the isolate coded C104 1 U2 exhibited necrosis symptoms, indicating pathogenicity, while the other isolates showed no necrosis symptoms, suggesting they were beneficial non-pathogenic microbial. Necrosis symptoms indicate the presence of pathogenic microbial, whereas their absence confirms the presence of beneficial microbial. This study provides a scientific foundation for developing innovative agricultural practices to enhance microbial diversity and ecosystem resilience in rice cultivation systems.